(untitled) (Biological Sciences - PJSIR, 1997)
Fish samples (Illisha africanai were collected from six man-made fish pond in Edo and Ondo States, Nigeria. Some orgaris of the fish, sediment and water from the fish habitat were analysed for Cd, Pb, Hg, Ca, Fe, Zn, Cu and Cr. Physico-chemical properties of water samples from the ponds were also re-corded. The concentration of the metals varied in the sediment water as well as in different organs of the fish. However, chromium was absent in all the samples. The descending order of metal concentration in fish organs was: gills, intestine, head and muscle. To avoid harmful accumulation of these metals in the human system, the gills and the intestine should preferably be discarded while processing fish for consumption. The head with a relatively high concentration of calcium might be useful in feed formulation.